GAMBARAN POLA TIDUR IBU YANG MENERAPKAN CO-SLEEPING & NON CO-SLEEPING - Debri Pristinella (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2020)
The role of a mother in a family is very complicated. To be able to perform these roles optimally,the mother needs physical and mental (psychic) energy management. Sleep is one of the mostimportant but often neglected as a physical and mental management. The problem of sleep inwomen is not a popular topic regarding the physical and mental well-being of womencomparing to other issues such as self-esteem. This study aims to explore the co-sleeping andnon-co-sleeping arrangements among mothers and the reasons behind the sleep settingscurrently apply. This study also aims to explore the sleep patterns and the correlation betweenthe reasons for sleep arrangements and their sleep patterns.Participants were 115 mothers with children age 6 months until 10 years old who live inJogjakarta. The survey was the data collection method. The research instrument was aquestionnaire on Sleep arrangements and Sleep Patterns, analyzed using descriptive analysisand Spearman correlation analysis.The results showed that 49.1% of mothers applied co-sleeping arrangements every day, while15.8% of mothers applied non-co-sleeping (sleeping separately with their children). The age ofthe subject's children ranged from 6 months to 10 years. The main reason for their sleeparrangement was “best for children's sleep quality” (61.4%). As many as 62.2% of mothershave poor and very poor sleep patterns. And this poor sleep pattern has a negative andsignificant correlation (-0.028) with the reason that sleep settings are “best for children's sleepquality”. It means that mothers arguing that the sleeping arrangements are best for theirchildren, tend to have a poor sleep pattern.